Effects of cold shortening and cooking rate on beef tenderness - D.A. King; T.L. Wheeler; M. Koohmaraie; Michael E. Dikeman; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 2002)
A study was conducted to determine if excised, cold-shortened muscle improves in tenderness with refrigerated aging. Changes in muscle tenderness due to cooking rates were also evaluated. Beef ribeye and shoulder clod muscles from the left side of 12 carcasses were removed 45 min postmortem and placed in an ice bath to induce cold shortening. Corresponding muscles from the right side were chilled conventionally on the intact side. One-inch steaks from these muscles were either frozen at 24 hours or aged for 14 days at 40ºF before being cooked and analyzed. Steaks were analyzed raw, or cooked to 160ºF internally in a oven at 200 (SLOW) or 500°F (FAST). Sarcomere length (degree of contraction), tenderness, and the extent of degradation of structural proteins were measured. Rapid chilling caused severe muscle contraction, which had a dramatic toughening effect. At 24 hours, the cold-shortened muscle showed less protein degradation than conventionally chilled muscle. After aging 14 days, tenderness had improved and protein degradation had occurred in both cold-shortened and conventional muscles, but degradation was still less in cold-shortened muscles. The improvement in tenderness and the increase in protein degradation from 1 to 14 days were equal between cold-shortened and conventional chilling treatments but the cold-shortened muscles remained tougher. FAST cooking resulted in greater cooking losses and greater sarcomere shortening than SLOW cooking. Cooking rate did not affect the tenderness of ribeye steaks, but SLOW cooking improved the tenderness of shoulder clod steaks that are higher in connective tissue. Extreme chilling conditions, which induce cold shortening, may reduce protein degradation beyond the effect of shortening. Although aging improved the tenderness of cold-shortened muscles, they remained tougher than their conventionally chilled counterparts.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Beef tenderness; Cooking rate; Cold shortening